Investigation of co-gasification of rubber seed shell and high density polyethylene mixtures - Chin, B.L.F. (Italian Association of Chemical Engineering - AIDIC, 2014)
In this study, the steam gasification of rubber seed shell and high density polyethylene mixtures were carried out in a thermogravimetric instrument coupled with mass spectrometer (TGA-MS) in argon atmosphere under non-isothermal condition to analyse the effect of the gas composition such as H2, CO, CO2, and CH4 when using different percentage of high density polyethylene of 0-40 weight in the mixtures and operating temperature of 700 -900 °C. The argon gas was supplied at a flowrate of 100 μL min-1 and the steam was generated from superheater at 110 °C whilst injected at flowrate of 3,000 μL h-1 into the TGA-MS system. The highest H2 and CO concentrations can be achieved at 56 and 29 vol in this system at a temperature of 900 C. Copyright © 2014, AIDIC Servizi S.r.l.